Influence of Library Environment, Internet Connectivity, Institutional Repositories on Utilization of Information Resources by Students of Federal Universities in South South, Nigeria - Udo-Anyanwu, Adaora J.; Kalu, Dolly C.; Ibegbulem, Kelechi (Communicate: Journal of Library and Information Science, 2023)
This study examined the influence of library environment, internet connectivity, and institutional repositories on utilization of information resources by students of federal universities in South South, Nigeria. The study was guided by three research questions and three hypotheses. The researchers adopted correlational research design. The instrument used to collect data for this study was a researchers’-made questionnaire which was rated using the four point Likert scale. The population of the study was 4,503 registered library users of the federal universities studied out of which a sample of 450. Proportionate and random sampling techniques were adopted. In analysing the data collected, Pearson Product Moment Correlation (PPMC) was used to answer the research questions while the hypotheses were tested at 0.05 alpha level using t-test statistics. The findings revealed that: there is a very high significant relationship between library environment and utilization of information resources; there is a very high significant relationship between internet connectivity and utilization of information resources and there is a very low no significant relationship between institutional repositories and utilization of information resources. Based on the findings, the researchers recommended that: conducive library environment should be provided for effective function and comfort of the library users; the library should be connected to an efficient internet service provider and made accessible to the students as far as they are within the school premises; and the university library should create awareness of the existence of institutional repositories so the students can make use of the resources contained therein.